Methodological and statistical quality in research evaluating nutritional attitudes in sports - Kouvelioti, R.; Vagenas, G. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
The assessment of dietary attitudes and behaviors provides information of interest to sports nutritionists. Although there has been little analysis of the quality of research undertaken in this field, there is evidence of a number of flaws and methodological concerns in some of the studies in the available literature. This review undertook a systematic assessment of the attributes of research assessing the nutritional knowledge and attitudes of athletes and coaches. Sixty questionnaire-based studies were identified by a search of official databases using specific key terms with subsequent analysis by certain inclusion-exclusion criteria. These studies were then analyzed using 33 research quality criteria related to the methods, questionnaires, and statistics used. We found that many studies did not provide information on critical issues such as research hypotheses (92%), the gaining of ethics approval (50%) or informed consent (35%), or acknowledgment of limitations in the implementation of studies or interpretation of data (72%). Many of the samples were nonprobabilistic (85%) and rather small (42%). Many questionnaires were of unknown origin (30%), validity (72%), and reliability (70%) and resulted in low (= 60%) response rates (38%). Pilot testing was not undertaken in 67% of the studies. Few studies dealt with sample size (2%), power (3%), assumptions (7%), confidence intervals (3%), or effect sizes (3%). Improving some of these problems and deficits may enhance future research in this field.